Growth and Yield of Different Castor Genotypes Varying in DroJght Tolerance - Lakshmamma, P; Prayaga, Lakshmi; Lavanya, C; Anjani, K (Annals of Arid Zone, 2016)
An experiment was conducted to evaluate twelve castor germplasm line~stOlerantto fusarium wilt and differing in bloom/ epicuticular wax load) under drought d ring rabi2005-06 in split plot design with three replications. Stress was imposed by wi oldingirrigation from 45-120 DAS (stress-I) or 65-120DAS (stress-2). Total dry matter ('IbM) andseed yield significantly reduced with stress. Control plants recorded 62.2 g see4 planrt,whereas stressed plants recorded 42.2, 42.4 g planri in stress-l and stress-2, re's~eCtivelY'Lines RG 2317,RG 923 recorded